gln3 Mutations Dissociate Responses to Nitrogen Limitation (Nitrogen Catabolite Repression) and Rapamycin Inhibition of TorC1 - Rai, Rajendra (American Society for Biochemistry and Molecular Biology, 2013)
The GATA family transcription activator, Gln3 responds to the nitrogen requirements and environmental resources of the cell. When rapidly utilized, “good” nitrogen sources, e.g., glutamine, are plentiful, Gln3 is completely sequestered in the cytoplasm, and the transcription it mediates is minimal. In contrast, during nitrogen-limiting conditions, Gln3 quickly relocates to the nucleus and activates transcription of genes required to scavenge alternative, “poor” nitrogen sources, e.g., proline. This physiological response has been designated nitrogen catabolite repression (NCR). Because rapamycin treatment also elicits nuclear Gln3 localization, TorC1 has been thought to be responsible for NCR-sensitive Gln3 regulation. However, accumulating evidence now suggests that GATA factor regulation may occur by two separate pathways, one TorC1-dependent and the other NCR-sensitive. Therefore, the present experiments were initiated to identify Gln3 amino acid substitutions capable of dissecting the individual contributions of these pathways to overall Gln3 regulation. The rationale was that different regulatory pathways might be expected to operate through distinct Gln3 sensor residues. We found that C-terminal truncations or amino acid substitutions in a 17-amino acid Gln3 peptide with a predicted propensity to fold into an α-helix partially abolished the ability of the cell to sequester Gln3 in the cytoplasm of glutamine-grown cells and eliminated the rapamycin response of Gln3 localization, but did not adversely affect its response to limiting nitrogen. However, overall wild type control of intracellular Gln3 localization requires the contributions of both individual regulatory systems. We also found that Gln3 possesses at least one Tor1-interacting site in addition to the one previously reported.